2015
DOI: 10.1016/j.talanta.2015.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channeled single chain variable fragment (scFv) based microfluidic device for explosives detection

Abstract: The development of explosives detection technologies has increased significantly over the years as environmental and national security agencies implement tighter pollution control measures and methods for improving homeland security. 2, 4, 6-Trinitrotoluene (TNT), known primarily as a component in munitions, has been targeted for both its toxicity and carcinogenic properties that if present at high concentrations can be a detriment to both humans, marine and plant ecosystems. Enabling end users with environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…Microfluidic technology confers advantages, including the precisely controlled fluidic environment and amiability to be automated, and has been developed and applied for molecular separations131415 and detections161718. For example, it has been shown that microfluidic devices can provide a much more accurate and automatic handling of fluids in the biopanning procedure192021222324.…”
mentioning
confidence: 99%
“…Microfluidic technology confers advantages, including the precisely controlled fluidic environment and amiability to be automated, and has been developed and applied for molecular separations131415 and detections161718. For example, it has been shown that microfluidic devices can provide a much more accurate and automatic handling of fluids in the biopanning procedure192021222324.…”
mentioning
confidence: 99%
“…Određivanje u specijalnim laboratorijama je skupo i nije fleksibilno. Osim toga, uzorkovanje može prouzrokovati greške [1,3,10,13,15-18, [25][26][27].…”
Section: Uvodunclassified
“…pak, neophodna su dalja istraživanja, naročito u oblastima masenog bilansa, smanjenja troškova i potpune mineralizacije [21]. Novije metode remedijacije su fluorescencija [6,10,27], elektrohemijske metode [25,27], fitoremedijacija [5,6,8,9,12], fotolitička transformacija [2,20], super kritična ekstrakcija tečnosti ugljendioksidom (SC-CO 2 ) [17], UC luminescencija [13,26,27], bioluminescencija [1,3], bioremedijacija [1, 4,5,7,8,11,18,[21][22][23][28][29][30], Fenton proces [2,5]. Svaka od ovih tehnologija poseduje niz prednosti, ali i mana kao što su previsoki troškovi, komplikovana aparatura, i zahtev za tehničko obučenim osobljem za efikasno funkcionisanje [22,26,27].…”
Section: Uvodunclassified
“…Microfluidic devices have proven their effectiveness in many disciplines of scientific research; proteomic analysis [ 7 ], macro-algae bloom investigations [ 8 ], biochemical mechanisms in 3D cell-based systems [ 9 ], paper-based microfluidic devices for biomarkers for disease and point of care diagnostics [ 1 ] and explosives detection [ 10 , 11 ]. Although traditional benchtop explosives detection systems and devices [ 12 ], and Singh’s method [ 13 ] continue to remain as the gold standard, microfluidic devices can in the near future provide a miniaturized, versatile, field portable platform capable of achieving the highest level of sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research within our group has focused on the development of technologies for the detection of explosives that provide; (1) a superior level of detection sensitivity; (2) flexibility to be miniaturized; (3) durability; (4) low cost to manufacture; and (5) high sample throughput. Investigations were conducted with a PMMA-modified 39-multichanneled microfluidic device for the detection of explosives [ 10 , 11 , 17 , 18 ] with targeted intentions for field applications. This report investigates a new design, fabrication, theoretical analysis and sensor integration of a 128-microchannel microfluidic device for explosives detection (specifically TNT) that offers the potential for enhanced sensor performance.…”
Section: Introductionmentioning
confidence: 99%